PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE TERHADAP PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - sampara palili (VICRATINA, 2018)
ABSTRACTThis article examines the application of cooperative learning model type example non example towards improving learning outcomes of class VIII students of Islamic Middle School Athirah Makassar. This research is a Classroom Action Research with a collaborative type. This research phase follows the model developed by Kemmis and Tanggart which is in the form of a spiral cycle which includes activities of planning, implementation, observation, and reflection. Data collection techniques used are: observation, interviews, documentation and test results. The results of the study indicate that the Application of the Cooperative Learning Model Example Non Example Type can improve students learning outcomes in the subjects of Islamic Religious Education by applying cooperative principles or components of Cooperative Type Example Non Example consistently. Improved learning outcomes can be seen from the original pre-cycle value of 73.92%, increasing to 75% in the first cycle of the first meeting and 76.44% in the second meeting, in the second cycle it increased to 79.44% in the first meeting and 83, 76 at the second meeting. And in Cycle III it increased again to 88.44% at the first meeting and 93.08% at the second meeting.Keywords: Cooperative Learning type example non example, Student Learning Outcomes